Empowering young entrepreneurs: Financing application programs and bazaar expos to increase competitiveness in Malang, East Java - Solekah, Nihayatu Aslamatis; Aisyah, Esy Nur (Community Empowerment, 2025)
This community service activity was conducted with an entrepreneurship community of budding young entrepreneurs. The activity aimed to increase the competitiveness of their startup businesses by assisting them in accessing financing at El Dinar Finance House in Malang City and strengthening product sales through promotional bazaar exposure. The Participatory Learning and Action (PLA) method was utilized, with implementation beginning with the preparation of business plan documents, practicing business plan presentations, fulfilling the requirements for financing applications, assessing financing eligibility, approving business financing, increasing sales through expo bazaars, and ensuring repayment of the obtained funding. The mentoring program successfully equipped young entrepreneurs with the skills to access financing, improve their marketing strategies, and gather direct consumer feedback. These improvements strengthened business competitiveness, while ongoing monitoring ensured the successful repayment of funding and facilitated effective collaboration among all stakeholders.